Inhaled corticosteroids and mortality in chronic obstructive pulmonary disease. Issue 12 (14th October 2005) - Sin, D D; Wu, L; Anderson, J A; Anthonisen, N R; Buist, A S; Burge, P S; Calverley, P M; Connett, J E; Lindmark, B; Pauwels, R A; Postma, D S; Soriano, J B; et al.
Abstract : Background: Clinical studies suggest that inhaled corticosteroids reduce exacerbations and improve health status in chronic obstructive pulmonary disease (COPD). However, their effect on mortality is unknown. Methods: A pooled analysis, based on intention to treat, of individual patient data from seven randomised trials (involving 5085 patients) was performed in which the effects of inhaled corticosteroids and placebo were compared over at least 12 months in patients with stable COPD. The end point was all-cause mortality. Results: Overall, 4% of the participants died during a mean follow up period of 26 months. Inhaled corticosteroids reduced all-cause mortality by about 25% relative to placebo. Stratification by individual trials and adjustments for age, sex, baseline post-bronchodilator percentage predicted forced expiratory volume in 1 second, smoking status, and body mass index did not materially change the results (adjusted hazard ratio (HR) 0.73; 95% confidence interval (CI) 0.55 to 0.96). Although there was considerable overlap between subgroups in terms of effect sizes, the beneficial effect was especially noticeable in women (adjusted HR 0.46; 95% CI 0.24 to 0.91) and former smokers (adjusted HR 0.60; 95% CI 0.39 to 0.93). Conclusions: Inhaled corticosteroids reduce all-cause mortality in COPD. Further studies are required to determine whether the survival benefits persist beyond 2–3 years.